Analysis of the problem of damage to facade systems as a result of military action - MOLODID, Oleksandr; PIPA, Volodymyr (Ways to Improve Construction Efficiency, 2025)
As a result of Russian aggression, Ukraine's civilian infrastructure has suffered extensive destruction and damage. Among the damaged objects, special attention is drawn to facade systems with thermal insulation, which proved to be unstable and vulnerable to non-design influences. The main components of facade systems that are damaged as a result of military actions have been identified. The impact of facade damage on the functional characteristics of the thermal insulation itself and the buildings as a whole has been established. The authors analysed the extent and overall quantitative assessment of the destruction of external wall structures with facade thermal insulation. In order to select the optimal technologies for restoring damaged facade systems, it is necessary to analyse the extent of destruction and the type of damage. The article analyses six main types of facade thermal insulation structural schemes that are most common in construction. The article examines the types and extent of damage depending on the location of the explosive element's impact relative to the building or directly on the building and the type of facade system. That is, the distance of the explosive element's impact was chosen as the criterion for classification: direct impact; distance from 25 to 50 m; distance over 50 m. Of particular interest for further research is the change in the scale and nature of destruction depending on the type of facade. As a result of the survey of damaged facade systems, the nature of the impact of shock waves was also revealed. The tasks for further scientific research have been formulated, namely the need to develop methods for repairing damage to facade systems caused by military actions. The most suitable methods for repairing facade systems damaged by military actions have been proposed. It has been established which type of facades are more susceptible to destructive effects from non-design influences.